Acetaminophen poisonings in Chilean healthcare settings: a 20-year story that does not end - Sanhueza-Aroca, Tamara; Verdugo-Silva, Samuel; Olate-Fica, Erwin; Rivas, Luisa; Muller-Ramirez, Claudio (Nepal Journal of Epidemiology, 2021)
Background: Acetaminophen (Paracetamol) is one of the most used and prescribed anti-inflammatory and analgesic drugs worldwide. It has become one of the main drugs related to accidental and intentional overdoses in many countries, including Chile. The objective of this work was to characterize acetaminophen poisonings occurred in Chile between the years 2001 and 2020.Methods: A retrospective study of acetaminophen poisonings among patients who were hospitalized in Chilean public and private hospitals was carried out between the years 2001 and 2020. Data was obtained from the Medical Outcome Statistical Report database. Inclusion criteria were cases of patients who were admitted into either public or private healthcare settings with diagnosis of acetaminophen poisoning according to the WHO ICD-10. Statistical analyses were run to establish associations between variables selected in the study.Results: A total of 2,929 cases were included in the study. 77 % of the cases corresponded to female patients (p